Effect of Initiation of Breast-Feeding on Maternal-Newborn Attachment: A Cross-Sectional Study - Preety Alagh; T. Jiwan; M.Mohi (International Journal of Midwifery Nursing And Practices, 2023)
Introduction: Breastfeeding is the best approach for meeting an infant's psychological and physiological needs. The importance of breastfeeding is best understood in light of the fact that early breastfeeding initiation and skin-to-skin contact soon after birth are essential for a newborn's survival. The connection between a mother and her infant plays a vital role in a child's growth and maturation. Hence, a research investigation was carried out to analyze how the act of beginning breastfeeding impacts the attachment between mothers and their newborns. Methods: The study employed a cross-sectional format to evaluate the correlation between the commencement of breastfeeding and the attachment between mothers and their newborns after childbirth. Total of 90 postnatal mothers were selected by convenience sampling technique. Postnatal mothers were contacted on 3rd day of delivery to ask about socio-demographic information and the time for initiation of breast feeding. After 6 weeks of delivery telephonic information was collected regarding maternal new-born attachment by standardized maternal postnatal attachment scale. Results: Maximum (62.2%) postnatal mothers initiated breastfeeding within 1-4 hours followed by >8 hours (14.4%), 5-8 hours (13.3%) and within 1hour (10%) respectively. Majority (96.7%) of postnatal mothers had very good level of maternal postnatal attachment with newborn. There was no significant effect of breastfeeding initiation time on maternal newborn attachment among postnatal mothers. Conclusion: There was no significant association found between initiation time of breastfeeding and maternal newborn attachment though the mean difference suggest the effect of initiation of breastfeeding on maternal newborn attachment postnatal mothers.
Keywords: Breastfeeding; Initiation time; maternal newborn attachment; postnatal mothers